2022
DOI: 10.3389/fpsyg.2022.986472
|View full text |Cite
|
Sign up to set email alerts
|

Care in the time of COVID: An interpretative phenomenological analysis of the impact of COVID-19 control measures on post-partum mothers’ experiences of pregnancy, birth and the health system

Abstract: BackgroundFindings suggest pandemic control measures have modified maternal health practices, compromising the quality of care provided to new and expectant mothers and interfering with their birthing experiences. For this reason, this study explored the lived experiences of post-partum Victorian mothers during the pandemic as well as the potential influence of control measures over their perceptions regarding the health system.MethodsThis study used a qualitative approach. Recruitment was conducted between Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…23 We can only assume that due to the COVID-19 pandemic, providing breastfeeding support was a lower priority for health services, as other studies have shown. 24 This was reflected in our study by the predominant experience of participants receiving insufficient breastfeeding support during the hospital stay. This may be partly due to the fact that just one International Board Certified Lactation…”
Section: Discussionmentioning
confidence: 81%
“…23 We can only assume that due to the COVID-19 pandemic, providing breastfeeding support was a lower priority for health services, as other studies have shown. 24 This was reflected in our study by the predominant experience of participants receiving insufficient breastfeeding support during the hospital stay. This may be partly due to the fact that just one International Board Certified Lactation…”
Section: Discussionmentioning
confidence: 81%
“…The number of parents who sustained their online connection regardless of the potential for negative impacts may be accounted for by a need to reduce their social isolation and to feel a part of the social world outside the boundaries of their residence. This may be particularly true at the intersection of the postpartum period, a time already marked by increased isolation and lower mental health status, and a global pandemic wherein sweeping changes were felt in each domain of the transition to parenting ( 34 , 41 ). These findings are consistent with participants in the current study; many reported curbing their online social media use to reduce the reported negative outcomes, while 45% retained their intensity of use regardless of the negative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the report of the benefit of non-visitation, other women reported greater intimacy and more time for themselves and their babies due to hospital calmness due to less capacity, and perceived professionals to be more relaxed because they treated only patients 21 . Congruent with this, the quietness in hospitalization due to the absence of visitors and the support of professionals represented a protective factor for puerperal women's mental health 22 .…”
Section: /15mentioning
confidence: 99%
“…The use of a mask was a barrier in the relationship between women and health professionals, as reported by pregnant women or women who gave birth during the pandemic. For them, the mask hindered the communication aspect, the recognition of professionals and dissociated the experience of childbirth 21 .…”
Section: /15mentioning
confidence: 99%